Desain Modul Praktikum Gerak Lurus Beraturan (GLB) Berbasis Smartphone Yang Digunakan Untuk Praktikum Di Luar Laboratorium - Renyaan, Novie Evelyn; Latununuwe, Altje; Latupeirissa, Asry N.; Malawau, Seska (Physikos: Journal of Physics and Physics Education, 2024)
Lurus Beraturan (GLB) practicum outside the laboratory. The trial was conducted in the form of a practicum carried out in elevators and on escalators using smartphones. To read the data from the smartphones, acceleration monitor software was used, where the measurement data is displayed graphically. Before trialing the practicum module, validation was carried out by two media experts with an average feasibility percentage of 96.25% and two material experts with an average feasibility percentage of 95.66%, both of which were declared valid. The module was then tested on 25 students from the Physics Education Study Program, class of 2022, to measure the students' understanding of the GLB concept. The research results show that students were able to understand the material and solve the given problems contained in the module. This is evident from the average initial practicum task score obtained by the students, which was 77.8 with a good category. Meanwhile, the average student score for the tasks after the practicum was 89.6, categorized as very good, and the average score for data analysis and graph interpretation was 81.